Measured loss evaluation of asymmetrical parameter type two-phase induction motor supplied with a three-leg voltage source inverter - Kongsuk, Prayad; Promkhun, Watcharin; Kinnares, Vijit (My University, 2014)
This paper presents the measured power losses of asymmetrical parameter type Two-Phase Induction Motor supplied with three-leg voltage source inverter. The comparison of the motor losses between balanced and unbalanced voltages supplied to both windings of the two-phase induction motor under variation of voltages at various inverter frequencies and various loads is given. A dSPIC microcontroller is employed to generate space vector pulse width modulation signals with switching frequency of 5 kHz for the two-phase three-leg VSI. The experimental results are shown that an unbalanced phase voltage case give lower losses than a balanced phase voltage case at the same modulation index, frequency and load. When decreasing main voltage winding from the rated value for both cases, there are minimum values of losses for each load torque value.